Twenty-one days of low-intensity eccentric training improve morphological characteristics and function of soleus muscles of mdx mice - Paulo S. Pedrazzani (Nature Portfolio, 2021)
Abstract Duchene muscular dystrophy (DMD) is caused by the absence of the protein dystrophin, which leads to muscle weakness, progressive degeneration, and eventually death due to respiratory failure. Low-intensity eccentric training (LIET) has been used as a rehabilitation method in skeletal muscles after disuse. Recently, LIET has also been used for rehabilitating dystrophic muscles, but its effects are still unclear. The purpose of this study was to investigate the effects of 21 days of LIET in dystrophic soleus muscle. Thirty-six male mdx mice were randomized into six groups (n = 6/each): mdx sedentary group; mdx training group-3 days; mdx training group-21 days; wild-type sedentary group; wild-type training group-3 days and wild-type training group-21 days. After the training sessions, animals were euthanized, and fragments of soleus muscles were removed for immunofluorescence and histological analyses, and measurements of active force and Ca2+ sensitivity of the contractile apparatus. Muscles of the mdx training group-21 days showed an improvement in morphological characteristics and an increase of active force when compared to the sedentary mdx group. The results show that LIET can improve the functionality of dystrophic soleus muscle in mice.